EFEKTIVITAS PENYULUHAN RABUN JAUH (MIOPIA) TERHADAP TINGKAT PENGETAHUAN SISWA KELAS VI SD ISLAM AL-AZHAR 21 KECAMATAN PONTIANAK TENGGARA TAHUN 2014 - ., Dwi Erlinda Putri (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Visual acuity is the primary indicator for healthy eye. Visual acuity will decrease if there is a process that impaires reflective media in the eye. Myopia is a type of refractive disorders that is common in school-age population. There are many risk factors for the progression of myopia, including a history of parental myopia, socioeconomic status, Intelligent Quotient (IQ), academic achievement, and close range activity, If the condition is not treated properly will have a negative impact on development child’s intelligence and learning processes which affect the quality, creativity, and productivity of the individual. Objective: To assess the effectiveness of nearsightness (myopia) counseling to the level of sixth grade students knowledge of Islam Al-Azhar 21 of Pontianak so as to prevent an increase in the number of myopia in children of primary school age. Methods: This study uses a quasi-experimental design using one-group pretest-posttest design that were conducted on 105 respondents. Hypothesis testing using the Wilcoxon test. Results: Before myopia counseling was conducted, only (1,9%) showed good knowledge. After the counseling session was conducted, most respondents (98,1%) showed good knowledge, and after two-weeks posttest (99,05%) showed good knowledge,too. Significancy value is 0,000 (p<0,05). This value indicates that there are changes in the level of knowledge on nearsightness(myopia) before,after, and after two weeks post-counseling. Conclusions Nearsightness (myopia) counseling is effective to increase respondents’ knowledge about eye health and myopia. Keywords: Myopia, Counseling, Child